2018
DOI: 10.1111/bph.14173
|View full text |Cite
|
Sign up to set email alerts
|

Serine proteinases in the turnover of the cartilage extracellular matrix in the joint: implications for therapeutics

Abstract: Cartilage destruction is a key characteristic of arthritic disease, a process now widely established to be mediated by metzincins such as MMPs. Despite showing promise in preclinical trials during the 1990s, MMP inhibitors for the blockade of extracellular matrix turnover in the treatment of cancer and arthritis failed clinically, primarily due to poor selectivity for target MMPs. In recent years, roles for serine proteinases in the proteolytic cascades leading to cartilage destruction have become increasingly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
32
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 120 publications
(143 reference statements)
1
32
0
Order By: Relevance
“…The role of MMPs in particular, as a class of enzymes that digest ECM components and cause cartilage degradation, is well established 56 . More recently it has emerged that other classes of enzymes such as serine proteinases are also upregulated in OA and may participate in proteolytic cascades leading to cartilage destruction 57 . All of the enzymes that are implicated in OA pathology also trigger pro-inflammatory signalling cascades through the activation of the PAR family of GPCRs 10 .…”
Section: Discussionmentioning
confidence: 99%
“…The role of MMPs in particular, as a class of enzymes that digest ECM components and cause cartilage degradation, is well established 56 . More recently it has emerged that other classes of enzymes such as serine proteinases are also upregulated in OA and may participate in proteolytic cascades leading to cartilage destruction 57 . All of the enzymes that are implicated in OA pathology also trigger pro-inflammatory signalling cascades through the activation of the PAR family of GPCRs 10 .…”
Section: Discussionmentioning
confidence: 99%
“…However, it is now clear that proteinases also perform precise and specific functions in both homeostasis and disease. The cleavage of triple helical collagens such as type II collagen (the major structural component present in cartilage) by the soluble collagenase subset of matrix metalloproteinases (MMP-1, MMP-8 and MMP- 13) represents an example of highly specific proteolysis whereby only a single peptide bond is cleavable under normal physiological conditions (3). This initial cleavage then leads to collagen denaturation, concomitant with increased susceptibility to other less specific proteinases and disassembly of the collagen network which is a requirement as cartilage is remodelled into bone during development, but also occurs during cartilage breakdown in degenerative scenarios such as rheumatoid arthritis (RA) and osteoarthritis (OA).…”
mentioning
confidence: 99%
“…We have demonstrated that an activator of PAR2, matriptase, induces cartilage destruction in a PAR2-and metalloproteinasedependent manner (10,11) and that a related serine proteinase, hepsin, can also activate PAR2 albeit in a markedly less efficient manner (12). Indeed, in complex disease environments (such as arthritis) multiple proteinases could be present to act on PAR2 making our understanding of how PAR2 is activated and regulated important (reviewed in (13)).…”
mentioning
confidence: 99%
“…Proteolytic turnover of the ECM in the inflamed joint is the focus of a review from Wilkinson et al . (), which explores the therapeutic approaches being used to target serine proteases in joint diseases. The targeting of other classes of proteases such as the MMPs, ADAMS and ADAMTSs, which play roles in various diseases via the use of monoclonal antibodies as therapeutic inhibitors, is discussed by Santamaria and de Groot ().…”
mentioning
confidence: 99%
“…This presents the opportunity to utilize the LAP technology to protect other molecules, such as cytokine or growth factor-based drugs, and for their release to be targeted, for example, in areas where there are high levels of proteases such as the arthritic joint. Proteolytic turnover of the ECM in the inflamed joint is the focus of a review from Wilkinson et al (2019), which explores the therapeutic approaches being used to target serine proteases in joint diseases. The targeting of other classes of proteases such as the MMPs, ADAMS and ADAMTSs, which play roles in various diseases via the use of monoclonal antibodies as therapeutic inhibitors, is discussed by Santamaria and de Groot (2019).…”
mentioning
confidence: 99%